2014
DOI: 10.1097/01.pra.0000454779.59859.f8
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Benefits and Risks of Yoga in Individuals with Bipolar Disorder

Abstract: Many individuals who self-identify as having BD believe that yoga has benefits for mental health. However, yoga is not without potential risks. It is possible that yoga could serve as a useful adjunctive treatment for BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…About five percent of yoga practitioners diagnosed with bipolar disorder have e.g. reported yoga-associated aggravations of their depressive symptoms (Uebelacker et al, 2014). This should be closely monitored in future RCTs.…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…About five percent of yoga practitioners diagnosed with bipolar disorder have e.g. reported yoga-associated aggravations of their depressive symptoms (Uebelacker et al, 2014). This should be closely monitored in future RCTs.…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Yoga has demonstrated significant improvement in depression as an adjuvant to antidepressants in several trials. [2432334647484950] Other demonstrated advantages of yoga in depression are improvement in anxiety,[3250] behavioral activation, and nonjudging facet of mindfulness. [47] Shahidi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Other populations seem to experience benefits that are similar to exercise alone, such as patients with bipolar disorder or lower back pain (Sherman et al, 2010;Cramer et al, 2013;Uebelacker et al, 2014). Buffart et al (2012) found that cancer patients reported a decrease in stress and anxiety post yoga treatments and only a moderate change in fatigue, quality of life, and social and emotional functioning.…”
Section: Yoga: Non-tactile Self-administeredmentioning
confidence: 99%